Survival Comparison Following Below-the-Knee Amputation in Diabetic Patients with and without Hemodialysis - Jaehyung Lee; Janghyun Kim; Sungkuk Chae; Seung ho Oh; Dongheon Cha (Foot & Ankle Orthopaedics)
Category: Diabetes; Other Introduction/Purpose: Foot ulcers and subsequent amputations are disabling complications in diabetic patients, and major amputations, including below-knee amputations, leave patients with catastrophic disabilities. Diabetes is the most common cause of causing end-stage renal disease which results in hemodialysis, and patients with diabetes on hemodialysis have a higher prevalence of several co-morbidities compared to those without diabetes. The purpose of this study is to compare survival rates after below knee amputation in patients with diabetes who are on hemodialysis and those who are not. Methods: This retrospective study was conducted on patients with diabetes who underwent below-knee amputation at a single tertiary hospital from 2005 to 2015. Exclusion criteria applied to patients undergoing amputation for reasons not directly related to diabetes, such as trauma or tumor. The survival rate analysis involved categorizing patients into hemodialysis and non-hemodialysis groups at the time of amputation. Within the hemodialysis group, further analysis was performed by subdividing patients into three groups based on the duration of dialysis: Group A (≤5 years), Group B (5-10 years), and Group C (>10 years). Results: A total of 98 patients were enrolled, with 54 in the hemodialysis group and 44 in the non-hemodialysis group. The hemodialysis group exhibited a significantly lower survival rate after below-knee amputation than the non-hemodialysis group (p=0.010 by the log-rank test). The 1-year survival rate was 66.7% in the hemodialysis group, contrasting with the non-hemodialysis group's rate of 90.9%. Similarly, the 5-year survival rate was 20.4% in the hemodialysis group and 52.3% in the non-hemodialysis group. Subgroup analysis revealed no significant differences in survival among the three subgroups based on the duration of dialysis before amputation (A vs. B, p=0.560; A vs. C, p=0.661; B vs. C, p=0.870 by the log-rank test). Conclusion: Among diabetic patients who underwent below-knee amputation, those on hemodialysis at the time of amputation showed lower 1- and 5-year survival rates compared to those without hemodialysis. There was no significant association between the duration of hemodialysis before amputation and survival.